The mediating role of learning goal orientation in the relationship between work engagement and innovative work behavior - Tan, Fee Yean; Johari, Johanim; Yahya, Khulida Kirana (2016)
Underpinned by the Broaden-and-Build Theory of Positive Emotions, this study posited that high level of work engagement will encourage academicians’ innovative work behavior through learning goal orientation. The mediating role of learning goal orientation in the work engagement and innovative work behavior relationship was also examined. Data were gathered through questionnaire survey completed by 265 academic staff from six public universities located in the northern and central regions of Peninsular Malaysia. The results indicated that academic staff members who are highly engaged at work would be more likely to exhibit a higher level of learning goal orientation, which ultimately tend to engage in innovative work behavior. Discussions enlighten learning goal orientation as a significant mediator in explicating the work engagement and innovative work behavior link, which provided full support to the underlying theory. Finally, practical ramifications and limitations of this study are also brought to fore.